Co-composting of cattle manure with biochar and elemental sulphur and its effects on manure quality, plant biomass and microbiological characteristics of post-harvest soil - Holatko, Jiri; Hammerschmiedt, Tereza; Kintl, Antonin; Mustafa, Adnan; Naveed, Muhammad; Baltazar, Tivadar; Latal, Oldrich; Skarpa, Petr; Ryant, Pavel; Brtnicky, Martin (Frontiers in Plant Science, 2022)
Improvement of manure by co-composting with other materials is beneficial to the quality of the amended soil. Therefore, the manure was supplied with either biochar, elemental sulphur or both prior to fermentation in 50 L barrels for a period of eight weeks. The manure products were subsequently analysed and used as fertilisers in a short-term pot experiment with barley fodder (Hordeum vulgare L.), carried out under controlled conditions in a growth chamber for 12 weeks. The sulphur-enriched manure showed the lowest manure pH and highest ammonium content. The co-fermentation of biochar and sulphur led to the highest sulphur content and an abundance of ammonium-oxidising bacteria in manure. The biochar+sulphur-enriched manure led to the highest dry aboveground plant biomass in the amended soil, whose value was 98% higher compared to the unamended control, 38% higher compared to the variant with biochar-enriched manure and 23% higher compared to the manure-amended variant. Amendment of the sulphur-enriched manure types led to the highest enzyme activities and soil respirations (basal, substrate-induced). This approach to improve the quality of organic fertilisers utilises treated agricultural waste (biochar) and a biotechnological residual product (elementary sulphur from biogas desulphurisation) and hence contributes to the circular economy.